Perancangan Sistem Pakar Untuk Mendiagnosa Penyakit Asam Lambung Dengan Metode Certainty Factor - Mhd Anshor Harahap; Ahmad Taufik Al Afkari Siahaan (Lembaga Pengembangan Kinerja Dosen, 2023)
An expert system is a computer-based system that can match or mimic the ability of an expert to solve a problem. This system is designed to mimic the expertise of an expert to answer questions and solve problems in the fields of health or medicine, business, economics and so on. The important role of an expert can be replaced by a computer program whose working principle is to provide solutions as done by the expert. Certainty Factor is a method that defines a measure of certainty of facts or rules to describe an expert's belief in the problem at hand. This system is web-based, so that later this system can be accessed by the wider community online via the internet anywhere and anytime. In dealing with a problem, answers are often found that do not have full certainty.1 This research aims to find out what factors cause the appearance of stomach acid disease through the Certainty Factor method.